Association of Dietary Habits and Interest for Food and Science versus Weight Status in Children Aged 8 to 18 Years. (21st January 2018) - Vanderhulst, Els; Faik, Aicha; Vansintejan, Johan; Van Rossem, Inès; Devroey, Dirk
Abstract : Introduction . This study aims to describe the association between dietary habits and weight status and the interest in food and science. Methods . We examined in a cross-sectional study 525 children aged between 8 and 18 years, who attended the Brussels Food Fair or the Belgian Science Day in 2013. They were divided into three groups: special interest in science, special interest in food, and a general control group. They completed a questionnaire, and body parameters were measured. The weight status of the children was identified using the growth charts and the calculated BMI. Results . In total, 525 children were included: 290 children in the reference group, 194 in the food group, and 41 in the science group. The prevalence of overweight and obesity was 28% in the general control group, 14% in the food group, and 15% in the science group. Breakfast and dinner were skipped more often by children with overweight or obesity. Children from the food and science groups had more sweets and meat, had less fruit, and skipped less meals. Conclusion . In our study, 28% of the reference group had overweight or obesity. The children with special interest in food or science differed from the control group.